Longitudinal associations across vocabulary modalities in children with autism and typical development. (February 2019) - Bottema-Beutel, Kristen; Woynaroski, Tiffany; Louick, Rebecca; Stringer Keefe, Elizabeth; Watson, Linda R; Yoder, Paul J
We examined differences between children with autism spectrum disorder and typically developing children over an 8-month period in: (a) longitudinal associations between expressive and receptive vocabulary and (b) the extent to which caregiver utterances provided within an "optimal" engagement state mediated the pathway from early expressive to later receptive vocabulary. In total, 59 children (28–53 months at Time 1) comprised the autism spectrum disorder group and 46 children (8–24 months at Time 1) comprised the typically developing group. Groups were matched on initial vocabulary sizes. Results showed that the association between early expressive and later receptive vocabulary was moderated by group. A moderated mediation effect was also found, indicating linguistic input provided within an optimal engagement state only mediated associations for the autism spectrum disorder group.